Kontribusi Dukungan Keluarga dan Sikap dalam Penguatan Mekanisme Koping Pasien HIV/AIDS di Poli VCT RSUD Raden Mattaher Jambi - Debbie Nomiko; Yellyanda Yellyanda; Bettywaty Eliezer; Ayu Maryastuty (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
Acquired Immunodeficiency Syndrome (AIDS) is a group of diseases that arise due to a decrease in acquired immunity. This research is descriptive-analytic with a cross-sectional design that aims to describe the relationship between family support and attitudes with coping mechanisms for HIV/AIDS patients at the VCT Poly Hospital Raden Mattaher Jambi in 2018. This study was carried out in April 2019. The population in this study was all 74 HIV/AIDS patients who visited the VCT Polyclinic. The sample in this study was taken as many as 34 people using the purposive sampling technique. The data collection technique that will be carried out is using a questionnaire and the data analysis used in univariate analysis and bivariate chi-square test. The results showed that the majority of respondents had good family support as many as 20 (58.8%), positive attitudes as many as 23 (67.6%) and good coping mechanisms as many as 18 (52.9%), there is a relationship between family support and coping mechanisms of HIV/AIDS patients with p-value 0.001, and there is a relationship between attitudes and coping mechanisms of HIV/AIDS patients with p-value 0.015. It is hoped that the results of this study will contribute to the nursing management of Raden Mattaher Jambi Hospital to improve nursing services for HIV AIDS patients at the VCT Polyclinic, especially those related to handling psychological problems (coping mechanisms) of patients and the related aspects in it.